Shifting Skill Needed For Future Accountant - Nadia Fathurrahmi Lawita; Anis Chariri (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
Entering the 4.0 and 5.0 revolution era, all professions face challenges and differences are likely to be replaced by the presence of current technologies. With rapid technological advances supported by the sophistication of robotics and artificial intelligence, the accounting profession has a 95% possibility that it will be replaced in the future, so accountants must prepare themselves to face such competition by acquiring a deeper understandingof the accounting information system that should be mastered by every accountant to produce information that is quick, effective, and efficient. This study uses a literature review method that analyzes all the results from previous journals and also from several books that are related to the topic. Whereas to deal with this situation, accountants need to prepare themselves throughvarious actions, specifically through knowledge procurement pertaining to Information Systems and Technology that is also supported by Technical and Ethical Competence, Intelligence, Creativity, Digital Quotient, Emotional Intelligence, Vision, and Experience.